Conceptualization of model of financial management in Romanian agriculture - Zhavoronok, Artur; Grosu, Veronica; Kholiavko, Nataliia; Zlati, Monica Laura; Cosmulese, Cristina Gabriela (Economic Annals-XXI, 2021)
Agriculture is one of the important sectors in Romania in terms of expanding the cultivated agricultural areas, the number of people working in this field and contribution of the branch to the national economy. Considering the socio-economic dimension of the branch, agriculture represents a viable opportunity in Romania given the qualitative land fund and the pedoclimate’s characteristic still favorable for obtaining financial performance in agriculture. Financial management is a challenge for economic operators in the agriculture. Due to the seasonal character of it, the managerial act of managing cash flow tables is difficult, and managers reach a high rate of indebtedness of the company. The seasonal stage of storage and trading of stocks represents for managers another challenge of financial management and brings with it randomized elements regarding the efficiency of the managerial act in the agricultural sector. The aim of the paper is to conceptualize a modern financial management model timed in agriculture to reduce financial pressure and allow managers to gain more efficiency in managing cash flow charts. The research uses empirical and analytical study methods including literature review, analysis of economic efficiency indicators obtained by agricultural companies in Romania, study of financial projections to identify significant vulnerabilities in cash flows and conceptualization of modern financial agriculture’s management model. The results of the study will be useful to managers of agricultural entities in their approach to efficiency and performance within the development of financial strategies.
Keywords: Agriculture; Financial Projections; Economic Model; Cash Flow Statement; Financial Management